Relações entre a formação e a prática do professor de língua estrangeira (inglês) para crianças - Rampim, Maysa Ferreira (Universidade Federal de São Carlos, 2010)
The present work describes a qualitative research on the training of teachers of English Language (henceforth EL) who deals with the Elementary School I. Initially, we intend to develop a historical background on the Postmodern Society on multicultural context. For this, there will be a brief history on the socio-cultural context of the child that is inserted in this society. After that, we will point to the importance of teaching foreign language for Children (hereinafter LEC), ie, the current reasons that have led to increasing numbers of children learning a foreign language (FL). Moreover, will be explicit the literacy teacher's LEC, in which the focus will be turned to the professional who teaches English classes in early grades. This route will remain to the desired skills that are expected from educators. Results of previous studies (Rocha, 2006; Santos, 2005) about teaching English to children point to the need to investigate more closely the skills of this professional, licensed by Modern Languages and Literatures programs. However, despite a degree in English during the graduation, the teacher receives the training to work only with elementary school students II. Moreover, the professionals of Education - enabled to work with children of elementary school I - are not trained in their graduation to teach foreign languages. Thus, both professionals - educated in Modern Languages and Literatures and Pedagogy - appear to be defective as regards their competence to teach English Language to children from 1st to 5th year. Thus, it was deemed important to monitor the work of three professors of LEC (English) in order to 1) identify the profile of the teacher who works with the teaching of English in the early grades, and, 2) investigate the process of teaching learning of Foreign Languages in Elementary School regarding the approach of the teacher who acts in this area. For data collection were selected two schools, one of the municipal and the other a private school had in it program the teaching of English for children from 1st to 5th year. In these schools, were investigated the work of three teachers, one educator and two graduates of Arts - Portuguese / English. Four instruments were used for data collection: observation of tuition through video recordings and audio, quizzes (with teachers) and interviews (with the coordinator and the teachers), to obtain data regarding the preparation of educators, as well as the goal pursued by the school to implement the teaching of English. Furthermore, were recorded daily research, aiming for better monitoring and observation of classes. Later there was a triangulation of data, which related to the literature, form the basis for the delivery of research.
Keywords: Língua inglesa - estudo e ensino; Letramento; Professores - formação; Crianças; Foreign language for children; English as a foreign language; Teacher training; Literacy; Elementary school; LINGUISTICA, LETRAS E ARTES::LINGUISTICA